Village Road Quality and Accessibility on Transforming Rural Development - Kamaludin, Ahmad Saifullah; Qibthiyyah, Riatu Mariatul (AGRARIS: Journal of Agribusiness and Rural Development Research, 2022)
Rural road infrastructure in Indonesia has increased significantly, especially during the last decade. This study presents an overview of how rural road quality and accessibility affected village economic transformation. It is the first empirical study in Indonesia addressing rural transformation. Village-level microdata, referring to the smallest administrative official, were utilized. Using a Random-Effects Panel Logit model, this study discovered that improving the type of road surface and accessibility for four-wheeled vehicles significantly increased the probability of village economic transformation. Different types of road infrastructure improvement affected the rural economic transformation both within and outside Java-Bali. Paved or concrete roads in Java-Bali had a higher marginal effect than on other islands, thereby increasing the likelihood of rural economic transformation. However, the road accessibility for four-wheeled vehicles in Java-Bali did not significantly affect the probability of rural economic transformation. Nevertheless, for villages on other islands, it did. Furthermore, the transformation significantly influenced other infrastructures, such as electricity coverage, market presence, information and communication technology (ICT), and flatland topography. Moreover, the road access to villages and the availability of water or irrigation significantly affected the probability of surviving in the agricultural sector. Following these findings, policymakers should prioritize villages’ infrastructure by considering different types of infrastructure provision across villages, referring to different infrastructure needs for Java-Bali and other islands.